ANNALYZE THE COMPARISON OF MARKET RISK IN FOREIGN EXCHANGE AND STATE OWNED BANKS IN INDONESIA (Case Study : 8 Foreign Exchange and 8 state owned bank period 2015-2018) - Lonteng, Esther Kezia; Tasik, Hizika H.D. Tasik (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: The development of the Indonesian banking industry has experienced lots of ups and downs, both that drive economic growth and those that are hampering. For the past few years Indonesian banking sector has been improving the performance and relience towards the economic stability in the present and future. By analyzing the market risk on both foreign exchange and BPD banks in Indonesia, this study aims to find out the comparison of which type of banks that affect the most. This study uses quantitative method with descriptive explanation. Secondary data are collected from Annual Reports of banks and analyzed with T-test, with the sample of 8 foreign exchange banks and 8 BPD banks. The finding of this paper is the effect market risk on private foreign exchange banks and state-owened banks is significantly has meandiference.Keywords: Banks, Market Risk